2018
DOI: 10.1002/lary.27437
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of 5‐Aminolevulinic Acid Is Sufficient for Photodynamic Therapy on Vocal Folds

Abstract: Objectives To evaluate the feasibility of topical photodynamic therapy (PDT) using 5‐aminolevulinic acid (5‐ALA) for vocal fold leukoplakia. Study Design Ex vivo and in vivo. Methods 5‐ALA was applied topically as a 20% solution to ex vivo canine vocal folds. The penetration depth and concentrations of 5‐ALA in tissue were quantified using frozen sectioning and fluorescamine derivatization after 5‐ALA contact incubation or topical spraying. Then, 5‐ALA solution was sprayed on leporine vocal folds once, twice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Conversely, more than half (57.1%) of the ALA‐PDT group showed an initial biopsy consistent with high‐grade dysplasia compared to 32.2% in the Laser group. The median follow‐up time was 4 years 1–24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, more than half (57.1%) of the ALA‐PDT group showed an initial biopsy consistent with high‐grade dysplasia compared to 32.2% in the Laser group. The median follow‐up time was 4 years 1–24 …”
Section: Resultsmentioning
confidence: 99%
“…Chen et al 23 waited for 1.5 h after topical application of oral cavity mucosal keratotic lesions. In 2019, Zhang et al 24 studied the concentration of ALA in tissue from topical sprays, in an ex vivo canine study. After 15 min of topical application with ALA, they found a depth of penetration over 2 mm and the same concentrations within the superficial 500 μm of epithelium regardless of exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Three hours after applying 5-ALA, PDT was performed using a 635 nm diode laser. Tissue analysis showed partial epithelial exfoliation after PDT, and the method was assessed as effective (23). Von Beckerath et al presented the results of the treatment of larynx tumors with PDT.…”
Section: Resultsmentioning
confidence: 99%
“…works are constantly being developed that describe the use of PDT in the case of neck cancer (10)(11)(12).…”
Section: Drug Biochemistrymentioning
confidence: 99%
“…In other studies, Zhang et al. (45) concluded that a 20% topical‐ALA solution is as therapeutically successful as systemically administered ALA, if exposure times are short (30 min), and if the photosensitizer was sprayed on the treatment area twice with an interval of 30 min between. Revealingly, this protocol, which involved PDT of the rabbit vocal folds, also resulted in less severe inflammation than that created by PDT after systemic ALA delivery.…”
Section: Discussionmentioning
confidence: 99%